Enhancing Junior High School Students’ Mathematical Understanding through Augmented Reality Media Using Assemblr Edu: A Development Study - Mukaromah, Dwi Sofiatul; Kumala, Fitria Zana; Sardido, Joannah Mae C. (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
Mathematical understanding ability is one of several basic mathematical abilities to be mastered and improved by students. Good mastery of this ability can support the development of advanced mathematical abilities. However, the students at SMPN 1 Paguyangan demonstrated low levels of mathematical understanding, which was partly due to monotonous lecture-based instruction and the rare use of interactive media to aid comprehension. This study aimed to develop Augmented Reality (AR)-based mathematics learning media using Assemblr Edu that were valid and effective in improving the mathematical understanding ability of ninth-grade students at SMPN 1 Paguyangan. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the AR-based mathematics learning media developed using Assemblr Edu for the topic of